Internal auditing as one of the most important internal mechanisms for embodying the principles of Corporate Governance - Zahra ABBAS; Nedjwa BENAOUIDA (Advanced Research in Economics and Business Strategy Journal)
The audit function is considered among the most important jobs in companies, because of the great interest in it and the many benefits it provides to companies such as fraud detection, carrying out control operations, and providing consulting services. Through this study, we aim to clarify the contribution of internal audit as a mechanism in the effective and good application of corporate governance, as it is an important mechanism of corporate governance embodiment mechanisms, the latter which seeks through auditing, especially internal auditing, to ensure effective control of the company's activity and the detection of fraudulent practices. The study concluded that the task and role of internal audit does not end at this point. Rather, the development of its standards has made it a tool for providing advisory services and solutions to the problems facing companies, and an effective element of control over their performance.